A Randomized Clinical Trial in Comparing the Effectiveness of Acceptance and Commitment Therapy and Metacognitive Therapy on Mind-Wandering Index in Adolescents - Tavighi, Mitra; Khalatbari, Javad; Ghorban Shiroudi, Shore; Rahmani, Mohamad Ali (International Journal of Applied Behavioral Sciences, 2019)
Introduction: Acceptance and commitment and metacognitive therapies are considered as third wave therapies. This study aimed to compare the effectiveness of acceptance and commitment therapy (ACT) and Metacognitive therapy (MCT) on the mind-wandering index in adolescents. Methods: In a randomized clinical trial, 45 female adolescents in Karaj were estimated using a Cloninger sample volume estimation method and were selected through purposive screening sampling. They were randomly assigned into three groups. Two ACT and MCT were presented to the experimental groups in the form of ten sessions of 1 hour. The data were collected at three time intervals through a demographic checklist, a structured clinical interview and a mind-wandering questionnaire. Analysis of covariance and Bonferroni analysis tests were used. Results: The primary outcomes showed that both ACT and MCT had a significant effect on the mind-wandering index (p<0.01), although this effectiveness was more favorable in the MCT group (P<0.05). The secondary outcomes also showed the stability of the results in the follow-up stage (p<0.05). Conclusion: The results of this study suggest the effectiveness of third wave therapies on psychological indices. These findings can be combined with clinical applications in planning new therapeutic and educational perspectives. Declaration of Interest: None